Modeling of Fiber-Constrained Planar PVC Gel Actuators - Yi Li; Xuxin Feng; Lixiang Zhu; Ziqian Zhang; Mingfei Guo; Zhixin Li; Yanbiao Li; Minoru Hashimoto (Nanomaterials, 2023)
In recent years, plasticized poly (vinyl chloride) (PVC) gel has attracted increasing attention in soft robotics. However, there is scarce research on the deformation mechanism and modeling of PVC gel actuators. In this study, to investigate the deformation mechanism of fiber-constrained planar PVC gel actuators, we propose a complex nonlinear model based on traditional thermodynamic electroactive polymer (EAP) multi-field coupling theory. The proposed model can reveal the dielectric breakdown strength of PVC gels and predict the deformation of planar PVC gel actuators with varying levels of pre-stretching. The theoretical results were in good agreement with the experimental results, indicating the feasibility of the proposed model.